2018
DOI: 10.1038/s41598-018-35069-0
|View full text |Cite|
|
Sign up to set email alerts
|

Silibinin, A Natural Blend In Polytherapy Formulation For Targeting Cd44v6 Expressing Colon Cancer Stem Cells

Abstract: Colon cancer stem cells have been attributed to poor prognosis, therapeutic resistance and aggressive nature of the malignancy. Recent reports associated CD44v6 expression with relapse, metastasis and reduced 5-year survival of colon cancer patients, thereby making it a potential therapeutic target. Thus, in this study, comprehensive prediction and screening of CD44v6 against 1674 lead compounds was conducted. Silibinin was identified as a potential compound targeting CD44v6. Inorder to substantiate these find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 56 publications
(66 reference statements)
0
17
0
Order By: Relevance
“…In the case of silibinin- PKC-η complex, it showed six bonds: the 3, 7 hydroxyl, and 1O groups of the benzopyran bonded with Asp 497 , Val 436 , Leu 486 , and the methoxyphenyl bonded with Asp 440 , whereas in the case of Ras-silibinin complex, it has been shown to have bonds of 7-OH and 1O atoms of the benzopyran with Lys 317 , Phe 228 , and Gly 213 , and the 1, 4 dibenzodioxins and an OH groups with Thr 235 . In addition, previous studies have reported a wide range of silibinin pharmacological activity, such as the STAT3 inhibitor 66 , anti-inflammatory, anti-PI3K-α and MAPK, cell cycle arrest at G 0 /G 1 phase and p38 MAPK inhibitor 67 , 68 , respectively. The silibinin have shown a broad-spectrum pharmacological effect on multiple drug targets and, therefore, can be utilized as a potential lead scaffold for further design of novel anticancer drugs with combined drug discovery and clinical study approach.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of silibinin- PKC-η complex, it showed six bonds: the 3, 7 hydroxyl, and 1O groups of the benzopyran bonded with Asp 497 , Val 436 , Leu 486 , and the methoxyphenyl bonded with Asp 440 , whereas in the case of Ras-silibinin complex, it has been shown to have bonds of 7-OH and 1O atoms of the benzopyran with Lys 317 , Phe 228 , and Gly 213 , and the 1, 4 dibenzodioxins and an OH groups with Thr 235 . In addition, previous studies have reported a wide range of silibinin pharmacological activity, such as the STAT3 inhibitor 66 , anti-inflammatory, anti-PI3K-α and MAPK, cell cycle arrest at G 0 /G 1 phase and p38 MAPK inhibitor 67 , 68 , respectively. The silibinin have shown a broad-spectrum pharmacological effect on multiple drug targets and, therefore, can be utilized as a potential lead scaffold for further design of novel anticancer drugs with combined drug discovery and clinical study approach.…”
Section: Resultsmentioning
confidence: 99%
“…apoptosis Induction by Silibinin ( 144 µg/ml) for 48-72h on SW480 and SW620 colorectal cancer cell lines was reported (21%-31% and 23%-40% late apoptosis, respectively) [36]. The total percentage of apoptosis in colorectal cancer cell line HCT116-CD44+ after induction of 120 µg/ml of Silibinin was 11.6% and 29.5% at 24 and 48h, respectively [37]. Our analysis revealed that late and total apoptosis percentage increased signi cantly to 25.5% and 32.36% in SPNs treated cells (28µg/ml) only after 24h.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the cell growth inhibition doses of Silibinin on SW480 and SW620 colorectal cancer cell line was evaluated by Henriette Kauntz and observed that it was 40-100 µg/ml within 8 days [36]. Shanaya Patel et.al also showed that Silibinin inhibited cell proliferation of HCT116-CD44+ subpopulation of colon cancer stem cells at 120 µg/ml [37]. In our previous study, we synthetized a polymersome nanocarrier that due to suitable properties(appropriate size, narrow size distribution, higher Encapsulation E ciency (EE) and Drug Loading (DL)) [29] we again used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative mRNA splicing of CD44 is mediated by epithelial splicing regulatory protein 1 (ESRP1), (Brown et al., 2011; Jeong et al., 2017; Preca et al., 2015; Yae et al., 2012) and several reports have suggested that the upregulation of ESRP1 is associated with poor prognosis of tumours (Jeong et al., 2017; Yae et al., 2012). A variety of CD44v isoforms generated by ESRP1, such as CD44v6 and CD44v8‐10, have been shown to be involved in multiple cellular functions, including proliferation, adhesion and metastasis (Hirata et al., 2013; Horibe et al., 2018; Ishimoto et al., 2011; Li et al., 2014; Nagano et al., 2013; Ogihara et al., 2019; Patel et al., 2018; Wada et al., 2018; Wu et al., 2015; Yoshikawa et al., 2013). In canine, it has been reported that CD44v3, v6 and v7 mRNAs are expressed in B‐cell lymphoma, and the expression of these mRNAs is associated with chemo‐resistance and a poor prognosis (Motegi et al., 2018).…”
Section: Discussionmentioning
confidence: 99%